The Reinier de Klerk House, a former country residence in Jakarta (Bulletin KNOB, 2005)
On the north coast of West-Java the East Indian Company 'VOC' founded the town of Batavia in 1619. A new fortification, 'the Castle', was built on the site where Jan Pieterz Coen destroyed the settlement Jacatra in the war against the Sultan of Banten.With the Castle in the farthest northeast point, the town of Batavia was laid out on both sides of the river Ciliwung; a rectangular urban grid with main and side canals, surrounded by town walls and on the west and east side of the Castle with fortified warehouses on the seaward sides.Already in the second half of the seventeenth century an outward move took place, because safety in the surroundings of Batavia had increased. The oppressive town within the walls, with the silted-up river and the badly drained, stinking canals was getting increasingly unpleasant.Reinier de Klerk was born in Middelburg in 1710 and had come to the Dutch East Indies as a navigating officer on a VOC ship; he had a successful career and died in 1780 in the function of governor-general. When he built the house, he had already been a member of the Council of the Dutch East Indies - an advisory board which the governor-general had to consult in the exercise of the supreme authority - for a considerable period of time.In the years 1755-58 De Klerk had acquired sufficient land on the Molenvliet, a dug canal to the south of Batavia, to be able to realise a large house with outbuildings and garden. It was just a quarter of an hour's drive by carriage from the walled town. The old Molenvliet ceased to exist a long time ago.Anonymous, cluttered buildings of a few floors high and half finished buildings alternate with modern high-rise; the country road has turned into a five-lane motorway. Unexpected, set back from the building line and surrounded by its own grounds, the former country residence is prominently present.Since 1925 until the early nineties the old country house and outbuildings functioned as the National Archives. It is the last remaining 18th-century example of this kind in Indonesia. The main building (the house), in a seemingly closed Dutch style, is characterised by an austere architecture.In 1994 the representatives of the Dutch business community decided to collect the required funds for the preservation and restoration of the historical country residence of Reinier de Klerk and to give it a new, useful function. On 22 August 1995, in the presence of Her Majesty Queen Beatrix, it was announced on location that enough funds had been collected to rehabilitate and preserve the complex for the future.The Indonesian government accepted the present. After the decision of restoring the former National Archives had been taken, the commissioning had been arranged, and a team of architects had been formed, a plan of approach was made and the research could start. The Indonesian government, notably the Archaeological Department, was an active discussion partner in the research.The main building was practically in its original condition, but it was dilapidated and in a bad state of repair. There were leaks in the gutters, sash windows were defective, window shutters did not function anymore, and there were problems with rising damp. However, the state of repair in the outbuildings was much worse; a distinction was made between the historical side wings, made of brick and plastered and with wooden joisting, and the twentieth-century extension dating from the time when the archives were established there, made of brick and plastered and with concrete floors.A new draining system in the form of a subterranean drainage with buffering capacity was constructed. The roof constructions were repaired or completely replaced by a new roof and roof covering. Window frames were repaired, the sash windows were renovated; the woodcarvings in the skylights of door frames were stripped of old layers of paint, whereby various techniques were tried out.The walls were cleaned and plastered again and everything was painted. The completion of the project took place in 1999, when the Minister of the Interior performed the festive opening; the Reinier de Klerk House now functions as accommodation for cultural events and exhibitions. In January 2002 the Indonesian-Dutch architects' team received the Unesco Award of excellence for the restoration.